The colorful world of David Samoylov’s poetry - Abisheva, Saule; Moldagali, Madina; Serikova, Samal (Przegląd Wschodnioeuropejski, 2023)
The article deals with the structure and semantics of color elements in the poetic texts by David Samoylov. Colorism manifests itself in three ways: as a color image recreated from the context, as substituted metonymy, and as words denoting color semantics. In this paper, using a continuous sample, the mechanism of manifestations of the basic monochromes “black – white” and the contaminated metatricolor “blue – green – red” is investigated on the basis of a complete collection of Samoylov’s poems. As a result of the article, a frequency dictionary of color elements was created, a semantic and structural analysis of five color images was carried out, and an ideological and thematic complex of the poet’s poetry was determined.